2017
DOI: 10.1158/0008-5472.can-17-0072
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 Upregulation by NANOG Promotes Multidrug Resistance and a Stem-like Phenotype in Immune Edited Tumor Cells

Abstract: Cancer immunoediting drives the adaptation of tumor cells to host immune surveillance. Immunoediting driven by antigen (Ag)-specific T cells enriches NANOG expression in tumor cells, resulting in a stem-like phenotype and immune resistance. Here, we identify HDAC1 as a key mediator of the NANOG-associated phenotype. NANOG upregulated HDAC1 through promoter occupancy, thereby decreasing histone H3 acetylation on K14 and K27. NANOG-dependent, HDAC1-driven epigenetic silencing of cell-cycle inhibitors CDKN2D and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 43 publications
4
74
0
Order By: Relevance
“…We next investigated the factor mediating histone deacetylation at the Atp5h and ATP5H loci during immune editing. Recently, we discovered that upregulation of HDAC1 is important for epigenetic reprogramming and acquisition of both stem-like properties and resistance to CTLs by CaSki P3 cells (27). Consistently, we observed HDAC1 upregulation upon in vivo immune editing of TC-1 tumor cells (Supplemental Figure 4).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…We next investigated the factor mediating histone deacetylation at the Atp5h and ATP5H loci during immune editing. Recently, we discovered that upregulation of HDAC1 is important for epigenetic reprogramming and acquisition of both stem-like properties and resistance to CTLs by CaSki P3 cells (27). Consistently, we observed HDAC1 upregulation upon in vivo immune editing of TC-1 tumor cells (Supplemental Figure 4).…”
Section: Resultssupporting
confidence: 82%
“…We discovered that immune editing alters the epigenetic landscape of tumor cells via histone deacetylase 1 (HDAC1) upregulation (27), which turns off ATP5H expression via promoter deacetylation. The epigenetic loss of ATP5H facilitates cancer immune escape and multimodal resistance to immunotherapy, chemotherapy, and radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the crucial role of Nanog in stemness maintenance of embryonic stem cell and cancer stem cell has been well established and extensively studied by other groups (Song et al, 2017; Jin et al, 2016; Noh et al, 2012; Chambers et al, 2003; Mitsui et al, 2003), we intend to further pinpoint whether SPOP deficiency upregulates prostate CSC properties in a Nanog-dependent manner. To this end, we examined the effects of SPOP deficiency in the presence or absence of Nanog on various prostate CSC traits.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Song et al . (32) found that NANOG‐mediated up‐regulation of antiapoptotic myeloid cell leukemia 1 protein leads to immune resistance and chemo resistance. Dhillon et al .…”
Section: Discussionmentioning
confidence: 99%